Chasma Australe, Mars: Formation by successive Headward thermo-erosional collapses - Gasselt, S. van; Jaumann, R. (Lunar and Planetary Institute, 2003)
The development of the south polar Chasma Australe re-entrant has been discussed for several years and a variety of theories including eolian, aquatic, subglacial and tectonic mechanisms have been proposed for its formation. Morphological observations and studies of recent imagery support the idea of successive headward erosion and removal of volatile–rich sub–surface material combined with collapse and eolian blow–out processes.